6502 Sayılı Tüketicinin Korunması Hakkında Kanun’un İspat Yüküne İlişkin Getirdiği Düzenleme - (:unkn) unknown (My University, 2018)
Satıcının ayıptan sorumlu tutulabilmesinin temel şartlarından biri, alıcının, kendisine tanınan süreiçinde, satın aldığı malı gözden geçirmesi ve bir ayıbın varlığını tespit ettiği takdirde, yine süresınırlarına da uygun olarak satıcıya bildirimde bulunmasıdır. Çok kere, diğer tüm şartların varlığınarağmen, malı gözden geçirme ve/veya bildirimde bulunma hususunda üzerine düşeni yerine getirmeyenalıcı, bunun sonucunda ayıptan doğan haklarını kaybetmektedir. Borçlar Hukukumuzda durum böyleolmakla birlikte, 6502 S. TKHK tüketici lehine ispat yükü başlığı altında farklı bir düzenleme getirerek,tüketicinin lehine bir tutum benimsemiştir. Avrupa Birliği Direktiflerinden esinlenilen bu hüküm,tüketici lehine taşıdığı önem nedeniyle, özellikle üzerinde durulması gereken bir hükümdür.

One of the basic conditions for the seller to be held accountable is that the purchaser shall review the goods purchased by him within the given time and if he detects the existence of a defect, he shall also notify the seller in accordance with the time limits. Many times, despite the existence of all other conditions, the buyer, who has not fulfilled his / her duties in reviewing and / or notifying the property, loses the rights arising from this. Although this is the case in our Law of Obligations, the 6502 TKHK has adopted an attitude in favor of the consumer by introducing a different regulation under the burden of proof in favor of the consumer. This provision, inspired by the European Union Directives, is a provision that should be elaborated upon especially because of its importance in favor of the consumer.
Burden of Proof Regulation Which Has Been Introduced by the Law 6502, Consumer Protection Act
Keywords: Hukuk